Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1152/physiolgenomics.00113.2019
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics analysis of human colon organoids identifies key transcription factors

Abstract: Organoids are a valuable three-dimensional (3D) model to study the differentiated functions of the human intestinal epithelium. They are a particularly powerful tool to measure epithelial transport processes in health and disease. Though biological assays such as organoid swelling and intraluminal pH measurements are well established, their underlying functional genomics are not well characterized. Here we combine genome-wide analysis of open chromatin by ATAC-Seq with transcriptome mapping by RNA-Seq to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…Here, we investigated whether the Krüppel-like factors (KLFs), a family of evolutionary conserved zinc finger transcription factors that regulate a variety of biological processes including proliferation, differentiation, and apoptosis [ 6 ], have an impact on CFTR expression and function. Among these TFs, we selected KLF2, KLF4, and KLF5 because of previous reports relating these TFs to CFTR [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and for their reported role on differentiation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we investigated whether the Krüppel-like factors (KLFs), a family of evolutionary conserved zinc finger transcription factors that regulate a variety of biological processes including proliferation, differentiation, and apoptosis [ 6 ], have an impact on CFTR expression and function. Among these TFs, we selected KLF2, KLF4, and KLF5 because of previous reports relating these TFs to CFTR [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and for their reported role on differentiation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KLF4 is induced transiently in response to wounding, and this phenomenon is absent in CF airway cells [ 8 ]. In parallel, genomic analyses of open chromatin in human tracheal epithelial cells revealed that KLF5 is part of a transcriptional network that represses CFTR gene expression [ 9 , 10 ] and such analyses predicted that in human intestinal organoids, KLF4 was among the top genes expected to be expressed at high levels, followed by CFTR [ 11 ]. Remarkably, another study reported that KLF2 is increased by 2.5-fold in CF mouse pre-adipocytes, precluding their differentiation [ 12 ], and yet another described that KLF2 expression is lost in CF cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since SPINT2 is also able to regulate ST14 activity in small and large intestines 16 we decided to use enterocytes as a model to test this hypothesis. In order to find common TFs regulators of SPINT2 / TMPRSS2 we performed two independent analysis: i ) A footprinting analysis of chromatin open regions using ATAC-seq data from Human Intestinal Organoids 17 identifying potential TF binding sites and ii ) Using scRNA-seq data from ileum derived organoids 18 we calculated the activity of transcription factors based on the gene expression of their targets using the SCENIC algorithm 19 . TF activities were then correlated to SPINT2 and TMPRSS2 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…For this work we used the following datasets available in public repositories: scRNA-seq profiles of Calu-3 and H1299 cell lines 22 ; scRNA-seq from ileum derived organoids 18 ; translatome and proteome quantifications of Caco-2 cell line 13 ; bulk RNA-seq profiles of lung samples of COVID-19 deceased patient autopsies 44 ; Peripheral Blood Mononuclear Cells 40 ; Nasopharynx samples from COVID-19 patients 38 ; Human Cell Landscape 25 ; The Cancer Genome Atlas. Tumor scRNA-seq datasets: Human Hepatocellular Carcinoma 51 , renal Clear Cell Carcinoma 50 , Lung Adenocarcinoma 53 , Colon Adenocarcinoma 52 , pancreatic cells from Diabetes Type 2 patients 54 ; ATAC-seq data from Human intestinal organoids 17 .…”
Section: Data and Script Availabilitymentioning
confidence: 99%
“…In humans, 17 KLFs have been identified, of which KLF2, KLF4, and KLF5 have been linked to pluripotency [ 11 ]. Notably, KLF2, KLF4, and KLF5 have also been somewhat associated with CF [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, KLF4 has been described as overexpressed in F508del-CFTR CFBE cells, and it has been shown to act as a negative regulator of wt-CFTR (but not of F508del-CFTR) in a process mediated by AKT / GSK3β signaling [ 20 ].…”
Section: Introductionmentioning
confidence: 99%